2018
DOI: 10.13075/mp.5893.00690
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the type of farmers’ low back pain

Abstract: The research revealed that individual farmers complained of low back pain significantly more often. The pain was usually defined as constant pain, chronic pain, acute pain or hip pain radiating to legs. Med Pr 2018;69(4):355-364.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…The results showed that subjects had had a history of LBP before, and it classified as chronic pain. Chronic pain is a type of pain caused by a prolonged non-ergonomic way of work [22], [23] and lasts for a longer duration of 1-3 months or even more [7]. [16].…”
Section: Effect Of Work Posture Improvement and Stretching Treatment mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that subjects had had a history of LBP before, and it classified as chronic pain. Chronic pain is a type of pain caused by a prolonged non-ergonomic way of work [22], [23] and lasts for a longer duration of 1-3 months or even more [7]. [16].…”
Section: Effect Of Work Posture Improvement and Stretching Treatment mentioning
confidence: 99%
“…Measurements using the Oswestry questionnaire found that the average LBP intensity of was 3.35 (very painful) with a range of categories from mildly to very painful. LBP experienced by subjects is mostly related to lifting and moving materials manually with odd work positions [23], [24] - [27]. LBP intensity was felt when the workers performed activities such as lifting weights, standing, sitting, walking, doing social activities and sleeping.…”
Section: Effect Of Work Posture Improvement and Stretching Treatment mentioning
confidence: 99%
“…There are improvements, causing body parts such as legs, arms and back to be more natural / ergonomic when carrying out activities to move minerals, transport and lift onto trucks. Ergonomic body position can reduce musculoskletal complaints [7], [8], [18], [19]. Qualitatively, ergo-physiological interventions reduce the level of risk from high to moderate levels.…”
Section: Work Posturementioning
confidence: 99%
“…Chronic LBP is a type of pain that is felt for longer ie 1-3 months or more [20], [21]. Chronic LBP pain is often caused by long-lasting work in a non-ergonomic [19], [23].…”
Section: Lbp Reductionmentioning
confidence: 99%
“…In a previous study on LBP in agricultural workers, it was reported that the incidence of LBP was higher in agricultural workers than other occupations. [22][23][24] In addition, LBP is related to work area 24 and lifting. 23 It is difficult to obtain a definite opinion on the relationship between agriculture and LBP in Japan, because most of the previous studies are from overseas and there are differences in crops, work characteristics, and work area among countries.…”
mentioning
confidence: 99%